Have a new kid by Friday : how to change your child's attitude, behavior & character in 5 days - Leman, Kevin (Grand Rapids, MI : Revell, 2008)
Today's kids are unionized, and they've got a game plan to drive you up the wall. But you don't have to let them call the shots.
Monday: where did they all come from? -- Tuesday: disarming the dude (or dudette) with the 'tude -- Wednesday: show me a mean teacher, and I'll show you a good one (it's all in the perspective) -- Thursday: But what if I damage their psyche? (Uh... what's a psyche?) -- Friday: the Doc is in... and it's you -- Ask Dr. Leman: A to Z game plans that really work -- Epilogue: fun day.
Includes bibliographical references and index.
Keywords: Discipline of children; Child rearing